148k views
0 votes
Solve this quadratic equation using the quadratic formula. 2x 2 - 10x + 7 = 0

2 Answers

4 votes

Answer:


x_1=4.158


x_2=0.8416

Explanation:

For an equation of the form
ax^2 +bx +c

The quadratic formula is


(-b\±√(b^2 -4ac))/(2a)

In this case the equation is:


2x^2 - 10x + 7 = 0

Then


a= 2\\b= -10\\c= 7

Therefore, using the quadratic formula we have:


x=(-(-10)\±√((-10)^2 -4(2(7)))/(2(2))


x=(5\±√(11))/(2)


x_1=4.158


x_2=0.8416

User Alex Choroshin
by
5.9k points
4 votes

ANSWER


x = ( 5 )/(2) - \frac{\sqrt {11} } {2} \: or \: x = ( 5 )/(2) + \frac{\sqrt {11} } {2}

EXPLANATION

The given quadratic equation is:


2{x}^(2) - 10x + 7 = 0

Comparing this equation to


a{x}^(2) + bx + c = 0

we have

a=2, b=-10 and c=7.

The solution is given by the quadratic formula;


x = \frac{ - b \pm \sqrt{ {b}^(2) - 4ac } }{2a}

We plug in the values to get,


x = \frac{ - - 10 \pm \sqrt{ {( - 10)}^(2) - 4(2)(7) } }{2(2)}

This implies that


x = \frac{ 10 \pm \sqrt{ {100} - 56 } }{4}


x = \frac{ 10 \pm \sqrt {44 } }{4}


x = \frac{ 10 \pm 2\sqrt {11 } }{4}


x = \frac{ 5 \pm \sqrt {11 } }{2}


x = ( 5 )/(2) - \frac{\sqrt {11} } {2} \: or \: x = ( 5 )/(2) + \frac{\sqrt {11} } {2}

User Lanoxx
by
5.8k points